'Failing Forward' Towards Which Europe? Organized Hypocrisy in the Common European Asylum System*. (18th May 2018) - Lavenex, Sandra
Abstract: Exposing the ideological conflicts involved in the creation of a Common European Asylum Policy, this article calls for an extension of classic integration theories to look beyond whether crises result in 'more' or 'less' Europe and to address the substance of European integration. Drawing on actor‐centered institutionalism and organizational sociology, the 'refugee crisis' is interpreted as a manifestation of the growing mismatch between the EU's normative striving towards a 'Union of values' and the political and institutional limits imposed. The result is organized hypocrisy: the concurrent reinforcement of protective claims and protectionist policies.